Rasakalpa And Pottali Kalpana In Rasashastra: A Scientific Review Of Their Preparation And Curative Potential - Kumar, Ajit; Dwivedi, Prabhat Kumar (Journal of Neonatal Surgery, 2025)
Rasashastra, an integral part of Ayurveda, focuses on the preparation and therapeutic utilization of mineral and metallic compounds. Rasakalpas are the unique formulations within this system, prepared using rigorous procedures that ensure safety, efficacy, and long shelf life. Among these, Pottali Kalpana is a highly evolved pharmaceutical technique involving compact spherical preparations made by enclosing a combination of detoxified metals, minerals, and herbs in a cloth or capsule-like form, followed by specific heating processes. These formulations are known for their high potency, rapid onset of action, minimal dosage requirements, and longer therapeutic retention.This review comprehensively explores the historical origins, classical references, pharmaceutical protocols, and clinical indications of Rasakalpa and Pottali Kalpana. It emphasizes the principles of Shodhana (detoxification) and Marana (incineration) which play a crucial role in transforming toxic metals into bio-assimilable therapeutic agents. The importance of Bhavana (trituration) with specific herbal juices to enhance therapeutic properties is also addressed.Moreover, the article integrates modern pharmaceutical insights and scientific validation efforts, highlighting the need for standardization, quality control, and pharmacological investigations. Clinical evidences indicate efficacy in various chronic and refractory conditions, including neurological, metabolic, and infectious diseases. As Ayurveda seeks global acceptance, a scientific approach to these traditional formulations can bridge the gap between ancient wisdom and modern medicine.In conclusion, Rasakalpa and Pottali Kalpana represent a sophisticated legacy of Ayurvedic pharmaceutics, and further research may contribute significantly to the advancement of integrative medicine.